Identification of weather patterns and transitions likely to cause power outages in the United Kingdom - Laiz Souto; Robert Neal; James O. Pope; Paula L. M. Gonzalez; Jonathan Wilkinson; Philip C. Taylor (Communications Earth & Environment, 2024)
Abstract Lightning strikes, snow, and wind are common causes of power system failures. Their frequency of occurrence varies depending on weather patterns and seasons. Here, we analyse the occurrence of thirty pre-defined daily weather patterns along with nearly 70,000 power system failures in the United Kingdom between 2010 and 2019 to investigate the predictability of weather-induced power outages. We identify high-risk weather patterns and pattern transitions for all seasons. Winter weather patterns characterized by high wind speeds and high precipitation volumes are responsible for many instances of power outages caused by wind, gale, and lightning strikes. Weather patterns with moderate to high snowfall are often linked to power outages caused by snow and ice. Because high-risk weather patterns can be forecast reliably with valuable lead time, clear links between specific patterns and transitions can significantly improve the preparedness of the United Kingdom and broader European distribution network operators for adverse weather conditions.